The American war in contemporary Vietnam transnational remembrance and representation - Schwenkel, Christina (Tracking globalization, 2009)
Christina Schwenkel explores how the 'American War' is remembered & commemorated in Vietnam. She looks at monuments, museums, cemetaries, battlefield tours & related sites, & offers an assessment of they ways in which Vietnamese & American memories of the war intersect.